Mapping the extent and nature of research examining health literacy and ethnic inequalities in maternity care: a scoping review - B. McEvoy; K. Watson; E. Aalai; G. Rowlands; H. Soltani; A.E.P. Heazell (BMC Health Services Research, 2026)
Abstract Background Globally, women from ethnic minority groups experience stark disparities in maternity care outcomes. While ethnic inequalities are complex, health literacy is a contributing factor. This scoping review aimed to map the extent and nature of research examining health literacy and ethnic inequalities in maternity care. The review sought to identify evidence gaps and inform the direction of future research in this area. Methods This scoping review followed methodological guidance published by Arksey and O’Malley (2005). A comprehensive search across 5 key databases and relevant grey literature identified 1,024 citations. Papers were reviewed against criteria for inclusion. Key study features were collated in a standardised data extraction form. Thematic analysis summarised key findings across the studies. Results The review included 14 papers that directly explored health literacy and ethnic inequalities in maternity care. The research had a wide geographical distribution and included quantitative ( n = 7), qualitative ( n = 4) and mixed methods research designs ( n = 3). Data were collected using a range of health literacy assessment tools. The focus of the research varied across the scope of maternity care, including pregnancy ( n = 7), the postnatal period ( n = 2) and the whole maternity continuum ( n = 5). Thematic analysis summarised four key findings: (i) Diverse definitions of health literacy; (ii) Health literacy challenges can disproportionately affect minority ethnic women; (iii) Poor health literacy can contribute to adverse outcomes and ethnic inequalities and (iv) Limited evaluation of health literacy interventions. Conclusions Health literacy is an important but understudied contributor to ethnic inequalities in maternity care. There is a need for high-quality in-depth research to explore health literacy and ethnic inequalities in maternity care. This will support the development of targeted, equity focused interventions. Optimisation of health literacy may serve to reduce persistent inequalities experienced by minority ethnic groups in maternity care outcomes.